2008
DOI: 10.1186/1471-2334-8-27
|View full text |Cite
|
Sign up to set email alerts
|

Roles of TNF-α gene polymorphisms in the occurrence and progress of SARS-Cov infection: A case-control study

Abstract: Background: Host genetic factors may play a role in the occurrence and progress of SARS-Cov infection. This study was to investigate the relationship between tumor necrosis factor (TNF)-α gene polymorphisms with the occurrence of SARS-CoV infection and its role in prognosis of patients with lung interstitial fibrosis and femoral head osteonecrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 25 publications
(39 reference statements)
0
36
0
2
Order By: Relevance
“…30 Additionally, previous studies have demonstrated that the polymorphism TNF-α gene may be attributed to the occurrence osteonecrosis in direct or indirect ways in SARS patients. 31 TNF-α can regulate the absorption activity of osteoclasts and the release of oxygen free radicals and lipid peroxidation, destroy bone and cartilage, which eventually result in ischemic necrosis of the femoral head. 32 Therefore, TNF-α has dual roles in both innate immunity and inflammatory pathology, and the gene regulation is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…30 Additionally, previous studies have demonstrated that the polymorphism TNF-α gene may be attributed to the occurrence osteonecrosis in direct or indirect ways in SARS patients. 31 TNF-α can regulate the absorption activity of osteoclasts and the release of oxygen free radicals and lipid peroxidation, destroy bone and cartilage, which eventually result in ischemic necrosis of the femoral head. 32 Therefore, TNF-α has dual roles in both innate immunity and inflammatory pathology, and the gene regulation is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors were involved in the aetiology of NONFH, among which evidences supporting the TNF-α gene-308 or -238 polymorphisms have been provided currently [29][30][31][32][33]. However, these distinct studies presented conclusions inconsistently.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, we used Hardy-Weinberg equilibrium (HWE) to analyze the genotype distribution and assess the reliability of subjects' selection for each study. Although the selection of controls in S. Samara et al [32] was likely to have poor quality (P < 0.05), the genotype distribution of the controls in Shixin Wang et al [33] did not significantly vary from the natural populations (P > 0.05) ( Table 2), which indicated that the selection of controls in in Shixin Wang et al [33] was acceptable for our analysis.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 87%
See 2 more Smart Citations